External quality assessment of Rift Valley fever diagnosis in countries at risk of the disease: African, Indian Ocean and Middle-East regions - (:unkn) unknown (My University, 2021)
Rift Valley fever virus (RVFV), an arbovirus belonging to the Phlebovirus genus of the Phenuiviridae family, causes the zoonotic and mosquito-borne RVF. The virus, which primarily affects livestock (ruminants and camels) and humans, is at the origin of recent major outbreaks across the African continent (Mauritania, Libya, Sudan), and in the South-Western Indian Ocean (SWIO) islands (Mayotte). In order to be better prepared for upcoming outbreaks, to predict its introduction in RVFV unscathed countries, and to run efficient surveillance programmes, the priority is harmonising and improving the diagnostic capacity of endemic countries and/or countries considered to be at risk of RVF. A serological inter-laboratory proficiency test (PT) was implemented to assess the capacity of veterinary laboratories to detect antibodies against RVFV. A total of 18 laboratories in 13 countries in the Middle East, North Africa, South Africa, and the Indian Ocean participated in the initiative. Two commercial kits and two in-house serological assays for the detection of RVFV specific IgG antibodies were tested. Sixteen of the 18 participating laboratories (88.9%) used commercial kits, the analytical performance of test sensitivity and specificity based on the seroneutralisation test considered as the reference was 100%. The results obtained by the laboratories which used the in-house assay were correct in only one of the two criteria (either sensitivity or specificity). In conclusion, most of the laboratories performed well in detecting RVFV specific IgG antibodies and can therefore be considered to be prepared. Three laboratories in three countries need to improve their detection capacities. Our study demonstrates the importance of conducting regular proficiency tests to evaluate the level of preparedness of countries and of building a network of competent laboratories in terms of laboratory diagnosis to better face future emerging diseases in emergency conditions.
Keywords: African Research